Epithelial-mesenchymal transition in colorectal cancer metastasis and progression: molecular mechanisms and therapeutic strategies - Fangfang Nie; Xue Sun; Jizhuo Sun; Jingdong Zhang; Yuanhe Wang (Cell Death Discovery)
Abstract Colorectal cancer (CRC) continues to be a major contributor to cancer-associated death, with metastatic disease posing substantial therapeutic challenges. The epithelial-mesenchymal transition (EMT) orchestrates the transformation of polarized epithelial cells into motile mesenchymal phenotypes, characterized by enhanced migratory capacity and invasive properties. EMT is central to CRC metastasis and progression, particularly concerning its contribution to invasion, internal infiltration, and colonization. Beyond metastasis, EMT facilitates cancer cells’ adaptation to diverse microenvironments, gain of stem cell-like characteristics, metabolic reprogramming, and evasion of therapeutic interventions. EMT signatures are emerging as potential prognostic biomarkers, offering valuable insights for real-time disease surveillance and personalized therapeutic strategies. Targeting EMT presents a promising therapeutic avenue to improve drug sensitivity and counteract resistance in CRC. This review systematically examines the molecular mechanisms regulating EMT in CRC, including key transcription factors; post-translational and epigenetic modifications; non-coding RNAs; and pivotal signaling pathways. Additionally, we evaluate the clinical implications of EMT in CRC progression and metastasis and critically assess emerging therapeutic strategies targeting EMT. This study lays the groundwork for developing more efficient interventions to mitigate metastasis and enhance treatment outcomes and patient survival by elucidating the intricate molecular networks that govern EMT and its contributions to CRC pathology.